2018
DOI: 10.1111/hel.12544
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori VacA, a distinct toxin exerts diverse functionalities in numerous cells: An overview

Abstract: Background Helicobacter pylori, gastric cancer‐causing bacteria, survive in their gastric environment of more than 50% of the world population. The presence of H. pylori in the gastric vicinity promotes the development of various diseases including peptic ulcer and gastric carcinoma. H. pylori produce and secret Vacuolating cytotoxin A (VacA), a major toxin facilitating the bacteria against the host defense system. The toxin causes multiple effects in epithelial cells and immune cells, especially T cells, B ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
76
0
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 67 publications
0
76
0
8
Order By: Relevance
“…VacA channels are formed in the cytoplasmic membrane and then enter the membrane of the endosomes and mitochondria through endocytotic vesicles [75]. VacA protein can separate the tight junction of the epithelial cells in gastric mucosa, As a result, VacA crosses through epithelial cells [76]. VacA has various effects on the host cell including cell vacuolization, alteration in mitochondrial membrane permeability, inhibition of T-lymphocyte activation and proliferation, and activation cell signaling [76].…”
Section: Vacuolating Cytotoxin a And Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…VacA channels are formed in the cytoplasmic membrane and then enter the membrane of the endosomes and mitochondria through endocytotic vesicles [75]. VacA protein can separate the tight junction of the epithelial cells in gastric mucosa, As a result, VacA crosses through epithelial cells [76]. VacA has various effects on the host cell including cell vacuolization, alteration in mitochondrial membrane permeability, inhibition of T-lymphocyte activation and proliferation, and activation cell signaling [76].…”
Section: Vacuolating Cytotoxin a And Gastric Cancermentioning
confidence: 99%
“…VacA protein can separate the tight junction of the epithelial cells in gastric mucosa, As a result, VacA crosses through epithelial cells [ 76 ]. VacA has various effects on the host cell including cell vacuolization, alteration in mitochondrial membrane permeability, inhibition of T-lymphocyte activation and proliferation, and activation cell signaling [ 76 ]. The membranes of VacA-induced vacuoles carry markers of late endosomes and lysosomes; therefore, VacA-induced vacuoles are derived from the endosome-lysosome pathway.…”
Section: Vacuolating Cytotoxin a And Gastric Cancermentioning
confidence: 99%
“…Once inside the cell, CagA initiates various signaling cascades by disrupting cell signaling networks that can lead to cytoskeletal rearrangements, altered cell polarity, and localized disruption of the epithelial barrier [11,78]. The VacA toxin (a pore-forming toxin) affects both epithelial cells and immune cells, including T cells, B cells, and macrophages [79]. This virulence factor dampens apoptosis and autophagy, while it promotes immune tolerance and as such enables persistent infection [73].…”
Section: H Pylori Virulence Factorsmentioning
confidence: 99%
“…In our study, the vacA s1 genotype was found to be more prevalent among PUD patients, however, there was no signi cant association between the presence of other virulence genes and clinical disease outcomes. The mosaic combination of s-and m-region allelic genotypes also has been established to be associated with the pathogenicity of H. pylori [42,43]. Accordingly, type s1m1 H. pylori strains express large amounts of VacA toxin and are strongly associated with a higher level of in ammation and mucosal ulceration, while vacA s1m2-harboring strains produce moderate amount of toxin and vacA s2m2 strains are virtually non-toxic and rarely associated to clinical outcome [44].…”
Section: Discussionmentioning
confidence: 99%